92 Digestawell® fiber improves in-vitro digestibility of alfalfa and coastal bermudagrass hay fed to horses. (29th July 2019) - Perron, Brittany S; Wagner-Wells, Ashley; Boyd, Jamie; Girard, Ivan; Guiterrez, Noheli; Burt, Justin C; Splan, Rebecca
Abstract: Enhanced microbial activity in the equine hindgut increases nutrient availability, reduces fecal waste, and adds value to low quality forages. The dietary supplement DigestaWell® Fiber (DF; fibrolytic cofactors: methionine and B vitamins), designed to increase microbial efficiency, has been shown to improve in-vitro digestibility of alfalfa and tall fescue forages after 48h incubation. The objective of this study was to determine if DF would improve in-vitro dry matter digestibility (DMD) and ADF digestibility (ADFD) of alfalfa and coastal bermudagrass hays incubated for 48h or 72h. Utilizing a crossover design, four mature Quarter Horse mares were fed 2% BW daily of alfalfa (AF; 32.8% NDF, 27.1% ADF) or coastal bermudagrass (CB; 63.2% NDF, 35.4% ADF) hay for 19d periods. DMD and ADFD were determined after 48h or 72h incubation with or without treatment (320mg/L DF) at 37.5°C in an ANKOM Daisy II incubator inoculated with 200g fresh feces. Forage samples were run in triplicate. Data were transformed to approximate normality, then analyzed using a repeated measures mixed model in SAS with main effects of forage, treatment, incubation time, and feeding period, and statistically significant interactions. Across incubation times, DMD was higher for AF than CB (P < 0.01; 49.4% vs 42.1%). Across forages, DMD was higher at 72h than at 48h incubation (P < 0.01; 47.5% vs 43.9%). DF improved DMD across forages at 48h (P = 0.03), but not at 72h (P = 0.47). Across incubation times, DF improved DMD of CB (P < 0.01), but not AF (P = 0.79). Additionally, across both forages and both incubation times, DF improved ADFD (P < 0.01). In conclusion, DF may improve microbial fermentation in the equine hindgut. Future research should investigate in-vivo effects of oral supplementation of DF on forage digestibility measures.